Eritrea : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2003)
This Selected Issues paper and Statistical Appendix examines the sustainability of the public finances in Eritrea. The paper analyzes monetary policy and management. It points out that the period since gaining independence in 1993 has not been long enough for the authorities in Eritrea to gain a full understanding of the functioning of the economy and develop the necessary skills and expertise to successfully implement the complex mix of economic, financial, and development policies needed to strengthen growth and reduce poverty. The paper also analyzes the determinants of inflation in Eritrea.